Assessment and nonpharmacological management for patients with cancer anorexia–cachexia syndrome: a best practice implementation project. Issue 4 (9th December 2022) - Zhang, Lanfang; Zhou, Chunlan; Wu, Yanni; Du, Dong; He, Ling; He, Lian; Xie, Guozhu; Wang, Li; Chen, Peijuan
ABSTRACT: Introduction and aims: Cancer anorexia-cachexia syndrome (CACS) is a common multifactorial syndrome, which affects up to 80% patients with advanced cancer. At present, evidence to support the benefit of pharmacological intervention in the management of CACS is limited. Patients would benefit from standard procedures for early assessment and identification of cancer anorexia-cachexia, and using nonpharmacological strategies to manage patients with CACS. This best practice implementation project aimed to implement an evidence-based practice in assessing and managing patients with CACS, thereby improving the compliance of clinical practice with the best evidence and the quality of life of patients with CACS. Methods: This was an evidence-based audit and feedback project that used a three-phase approach at a public hospital in China. Phase 1 included the development of seven evidence-based audit criteria and carrying out a baseline audit on 30 patients using the JBI's Practical Application of Clinical Evidence System in the Department of Radiation Oncology of Nanfang Hospital. Phase 2 utilized the Getting Research into Practice component of the Practical Application of Clinical Evidence System to identify barriers to compliance with best practice principles and developed strategies and resources to improve compliance. Phase 3 involved conducting a follow-up audit using the same sample size and audit criteria to assess the results of interventions implemented to improve practice and identify issues that would be addressed in future audit. Results: The compliance rates of audit criteria 1, 2 and 6 were 100% at both baseline and follow-up audit. After the application of evidence, the compliance rate increased from 0 to 100% for audit criterion 3, from 0 to 76.6% for audit criterion 4, from 23 to 70% for audit criterion 5, and from 0 to 40% for audit criterion 5. Conclusion: The best evidence for the assessment and nonpharmacological management of cancer patients with CACS can improve clinical practice, the quality of clinical nursing, and patient satisfaction. The application of electronic informatization promotes the implementation and maintenance of best practice.